Endophthalmitis in Eyes with Osteo-odonto Keratoprosthesis. (2nd January 2022) - Rishi, Pukhraj; Rishi, Ekta; Manchegowda, Pradeep; Iyer, Geetha; Srinivasan, Bhaskar; Agarwal, Shweta
ABSTRACT: Aim : To analyze the incidence, microbiological profile, risk factors, and outcomes in eyes with osteo-odonto keratoprosthesis (OOKP) developing endophthalmitis. Methods & material : Retrospective review of medical records of patients presenting between 2003 and 2013 with OOKP and endophthalmitis was undertaken after obtaining IRB approval. Patient demographics, clinical features, microbiological evaluation, treatment details, and outcomes were analyzed. Results : Of 92 eyes with OOKP, 8 (9%) had endophthalmitis. Indications for OOKP included Steven–Johnson syndrome (SJS; n = 6; 75%) and chemical injuries (n = 2; 25%). The mean duration from OOKP surgery to endophthalmitis was 49.4 ± 32.3 months. Seven of eight eyes had associated laminar resorption. Endophthalmitis resolved with conservative management in three eyes. Lamina removal was required in three eyes; one eye underwent evisceration. At presentation, mean BCVA was 2.76 ± 0.24 logMAR that improved to 2.48 ± 1.0 logMAR after intervention. Mean follow-up was 12.6 ± 13.2 months. Conclusion : Endophthalmitis portends a grave prognosis for eyes with OOKP. The most important risk factors are SJS (75%) and lamina resorption (88%).